1962
DOI: 10.1017/s0021859600013915
|View full text |Cite
|
Sign up to set email alerts
|

Selection criteria in grass breeding. I

Abstract: 1. To evaluate selection criteria in grass breeding, a series of investigations was conducted measuring plant performance in a wide range of field environments.2. This paper reports on the behaviour of one variety of Lolium perenne, S. 24, grown in a logarithmically related series of densities and frequently defoliated for 2 years. Half the plots received only natural rainfall, the rest were irrigated so that the calculated soil moisture deficit did not exceed 2 in.3. In 1958, with little effect of irrigation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

1964
1964
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 21 publications
4
33
0
Order By: Relevance
“…Testing under sward conditions is usually deferred to the progeny assessment phase but even here, due to restrictions imposed by low seed supplies, the tests are confined to relatively small plot trials . It has long been recognised that there are serious limitations in assessing performance under such restrictive conditions when extrapolating to the performance on the farm (JENKIN, 1931 ;LAZENBY & ROGERS, 1962.1964,1965ENGLAND, 1967 ;WRIGHT & DO VALLE RIBIERO, 1973 ;SEDCOLE & CLEMENTS, 1973) . Thus although LAZENBY (1957) initially showed that the ranking of perennial ryegrass (Lolium perenne) genotypes does not change when evaluated in spaced plants, rows, drills and broadcast plots, later studies (LA-ZENBY & ROGERS, 1965) indicated that spacings of 22 cm or less between plants were necessary for assessing sward yielding ability .…”
Section: Introductionmentioning
confidence: 99%
“…Testing under sward conditions is usually deferred to the progeny assessment phase but even here, due to restrictions imposed by low seed supplies, the tests are confined to relatively small plot trials . It has long been recognised that there are serious limitations in assessing performance under such restrictive conditions when extrapolating to the performance on the farm (JENKIN, 1931 ;LAZENBY & ROGERS, 1962.1964,1965ENGLAND, 1967 ;WRIGHT & DO VALLE RIBIERO, 1973 ;SEDCOLE & CLEMENTS, 1973) . Thus although LAZENBY (1957) initially showed that the ranking of perennial ryegrass (Lolium perenne) genotypes does not change when evaluated in spaced plants, rows, drills and broadcast plots, later studies (LA-ZENBY & ROGERS, 1965) indicated that spacings of 22 cm or less between plants were necessary for assessing sward yielding ability .…”
Section: Introductionmentioning
confidence: 99%
“…There were significant DxV interactions on each annual total. Splitting up the interaction sums of squares revealed in each case, as with dry-matter yields per unit area (Lazenby & Rogers, 1962), the majority of the interaction to be attributable to a relative varietal behaviour at 27 in. being atypical.…”
Section: Nitrogen Production Per Unit Areamentioning
confidence: 95%
“…The first comprised one variety of L. perenne, S 24, sown at five densities, both with and without irrigation (Lazenby & Rogers, 1962). In the second, four varieties of L. perenne (S 24,Irish,Kent and S 23) were planted at four densities, half the plots being irrigated in the third and final year of the trial (Lazenby & Rogers, 1964).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations